The effects of technology on health and physical activity: A qualitative study - Orhan, Bekir Erhan; Karaçam, Aydın; Çetin, Arif (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to explore how technological devices influence individuals’ physical activity and overall health, identifying both the positive and negative effects of technology use on well-being. A qualitative design employing semi-structured interviews was used with a convenience sample of 100 participants aged 18–52 years (M ± SD = 26.3 ± 8.5). The sample consisted of 51% females and 49% males. The interviews explored participants’ experiences and perceptions of how technological devices influence physical activity and overall well-being. Data were transcribed, coded, and thematically analyzed to identify both positive and negative effects. The findings indicated that excessive use of smartphones, computers, and gaming devices contributed to sedentary lifestyles, musculoskeletal discomfort, psychological fatigue, and reduced social interaction. However, participants also reported that technology can support physical activity through fitness apps, wearable devices, and online exercise platforms. Suggested strategies to mitigate adverse effects included regulating screen time, correcting posture, practising mindful technology use, and incorporating breaks for physical movement. Technology has a dual influence on health and physical activity, acting both as a barrier and a facilitator. Striking a balance between use and overuse is essential to ensure positive outcomes. Public health initiatives and educational programs should emphasize responsible technology engagement and encourage strategies that promote active lifestyles.